Phytoremediation of heavy metal pollution: a case study - Vashegyi, Ágnes (Acta Biologica Szegediensis, 2005)
In the framework of a phytoremediation project for decontamination of heavy metal-polluted environment, two experimental fields were monitored for the existing plant species and soil contaminants. At the site of the slurry deposition from the oxbow lake at Mártély, mainly Zn, Pb and Cr were determined as pollutants. In situ, a number of plant species were found, most importantly Salix species. At the other study site, at Almásfüzitô, „red sludge” deposition from aluminum earth factory was monitored. In laboratory investigations, Salix species were found as Zn-accumulator species, therefore their capabilities and diversity were further investigated in 6 clones of Salix alba, as well as in S. caprea and S. viminalis rooted, grown and loaded with heavy metals under controlled conditions.